Contemporary migration patterns in the prevalence of Helicobacter pylori infection: A systematic review. Issue 3 (18th January 2017) - Morais, Samantha; Costa, Ana Rute; Ferro, Ana; Lunet, Nuno; Peleteiro, Bárbara
Abstract: Background: A rapid growth in the number of international migrants over the past years has occurred with most traveling to more affluent settings. As Helicobacter pylori infects over half of the adult population and its prevalence is higher in developing countries, understanding the prevalence of infection in migrants can provide insight into future trends in the burden and management of infection. We aimed to describe the prevalence of H. pylori among migrants through a systematic literature review. Methods: We searched PubMed ® from inception to September 2015 to identify studies reporting the prevalence of H. pylori in international migrants according to country of birth for first‐generation, and country of birth and parents' nationality for successive generations. Comparable data from origin and destination populations were obtained from the same studies or, when not present, from a previous systematic review on H. pylori worldwide. Results: A total of 28 eligible studies were identified with data for 29 origin and 12 destination countries. Two studies that evaluated refugees presented prevalences of infection higher than both the origin and destination countries. Otherwise, the prevalences among migrants were generally similar or below that of the origin and higher than the destination. Second‐ or more generation had lower prevalences compared to first‐generation migrants. Conclusions: Our study findings are consistent with what would be expected based on the prevalence of H. pylori worldwide. The results of this review show that migrants are particularly at risk of infection and help to identify gaps in the knowledge of migrants' prevalence of infection globally.